The new boy - Stine, R.L (New York, Pocket Books, 1994)
What a hunk! When handsome, mysterious Ross Gabriel comes to Shadyside High, all the girls want to date him ... even those who already have boyfriends! Janie, Eve and Faith go so far as to make a bet ... which one of them will he go out with first? But then the murders begin, and it starts to look like dating Ross means flirting with a gruesome and untimely death
Keywords: English fiction